Extracellular vesicles in endometriosis: role and potential - Chu, Xinying; Hou, Menghui; Li, Ying; Zhang, Qingyue; Wang, Shuxin; Ma, Jing (Frontiers in Endocrinology, 2024)
Endometriosis is a chronic inflammatory gynecological disease, which profoundly jeopardizes women's quality of life and places a significant medical burden on society. The pathogenesis of endometriosis remains unclear, posing major clinical challenges in diagnosis and treatment. There is an urgent demand for the development of innovative non-invasive diagnostic techniques and the identification of therapeutic targets. Extracellular vesicles, recognized for transporting a diverse array of signaling molecules, have garnered extensive attention as a novel mode of intercellular communication. A burgeoning body of research indicates that extracellular vesicles play a pivotal role in the pathogenesis of endometriosis, which may provide possibility and prospect for both diagnosis and treatment. In light of this context, this article focuses on the involvement of extracellular vesicles in the pathogenesis of endometriosis, which deliver information among endometrial stromal cells, macrophages, mesenchymal stem cells, and other cells, and explores their potential applications in the diagnosis and treatment, conducing to the emergence of new strategies for clinical diagnosis and treatment.